Socio-economic considerations and potential implications for gene-edited crops - Ludlow, Karinne; Smyth, Stuart; Falck-Zepeda, José B. (Office of the Texas State Chemist, 2021)
Regulatory clarity and efficiency are increasingly important for the successful commercialization of technologies resulting from public and private R&D investments. This article examines recent developments in the movement away from mostly science-based risk assessment regulatory and variety approval systems focusing on human and animal health and environmental safety to hybrid systems that include assessment of socio-economic considerations allowed for under the auspices of the Cartagena Protocol on Biosafety. We propose that socio-economic consideration assessments can be grouped into three methodological categories: empirically based, legally grounded and consensus approaches. Our exploration of developments in the three categories reveals gaps in data, consistency and methodology rigor, that must be addressed for efficient and reliable socio-economic consideration assessment. We assess the potential impacts of these gaps on the regulation of gene-edited crop varieties, concluding that if gene-edited crops are regulated as genetically modified crops, they will endure the same fate, that is, lengthy regulatory approval processes and failure to be commercialized. The end result being that the regulatory burdens in potential adopting and food insecure countries will prevent important new crop varieties from reaching farmers and producers for their use.